ANALISA KEPUTUSAN INVESTASI KEUANGAN ADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UPN “VETERAN” JAWA TIMUR - Elsiva Mujityara; Eko Purwanto (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Investment is an investment for profit in a certain period. This study aims to analyze financial literacy, financial efficacy, and financial behavior on student investment decisions. The population in this study were students of the Faculty of Economics and Business at UPN "Veteran" East Java who had invested. The sampling technique usedmethod non-probability sampling and determined by purposive sampling. The sample used in this study is 96 respondents who have invested and are still active students of the economics and business faculty at UPN "Veteran" East Java. This study uses Partial Least Square (PLS). Based on the results of the research that has been done, it shows that the variables of financial literacy and financial behavior have an effect on student investment decisions. While the financial efficacy variable has no effect on student investment decisions.